2019
DOI: 10.5430/jms.v10n3p48
|View full text |Cite
|
Sign up to set email alerts
|

Employee’s Perception on Workplace Gossip in the South African Public Sectors: The Implication on Job Performance

Abstract: Gossip is pervasive in any working environment. Sketching upon the existing and scant body of research knowledge surrounding the subject of gossip, the current qualitative study undertaken critically assessed how the employees protrude themselves after being victims of gossip in a workplace. This study examined the influence of workplace gossip on the job performance of employees within selected municipalities in South Africa. The researcher intended to establish the likeliest behaviour of municipality employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Workplace gossip is common in the work environment; it is one of the channels for employees to communicate in the organization, and plays a very important role in the organization ( Irvine and Blessing, 2019 ). Studies indicated that employees spend approximately 65% of their working time on gossip ( Ye et al, 2019 ), and more than 95% of employees participated in workplace gossip ( Grosser et al, 2012 ), which further demonstrates the prevalence of workplace gossip.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace gossip is common in the work environment; it is one of the channels for employees to communicate in the organization, and plays a very important role in the organization ( Irvine and Blessing, 2019 ). Studies indicated that employees spend approximately 65% of their working time on gossip ( Ye et al, 2019 ), and more than 95% of employees participated in workplace gossip ( Grosser et al, 2012 ), which further demonstrates the prevalence of workplace gossip.…”
Section: Introductionmentioning
confidence: 99%